Effect of aluminum and indium co-doping on zinc oxide films prepared by dc magnetron sputtering - Tohsophon T. (2014)
Aluminum and indium co-doped zinc oxide (AIZO) thin films were prepared by direct current (dc) magnetron sputtering on glass substrate in pure argon atmosphere. Three inches of zinc oxide ceramic with 0.5 wt.% of aluminum and indium doping was used as a target in static mode. The influence of sputtering conditions i.e. substrate-target distance, pressure and power on AIZO films was studied. The electrical resistivity and microstructure of thin films were investigated by the four point probe technique and the scanning electron microscope, respectively. The optical transmittance of AIZO films was measured by UV visible spectrophotometer in the wavelength of 300-1100 nm. Depending on the deposited conditions, highly transparent films up to 80% with low resistivities in the range of 2.6-7.9 × 10- 4 Ω cm were achieved at room temperature. Possible mechanism in the processing which, ultimately, determines the physical properties of AIZO films will be discussed. © 2011 Elsevier B.V. All rights reserved.